Addressing the Obstacles to the Use of Social Media in Promoting Entrepreneurship in Lafia Metropolis: Challenges and Remedies - Garba, Keje Tsilla Garba; Umoh, Ekong Raphael Umoh (African Journal of Stability and Development (AJSD), 2025)
This paper explored the challenges associated with using social media for entrepreneurship promotion in Lafia metropolis and identified potential remedies to overcome these obstacles. Employing a mixed-method research design, the study surveyed 340 randomly selected entrepreneurs and conducted in-depth interviews with five entrepreneurs to gather both quantitative and qualitative data. The findings reveal that high data costs and a lack of adequate knowledge and skills in social media usage are significant barriers to the effective deployment of social media in entrepreneurial strategies. The study further suggests that targeted interventions, including affordable data plans and comprehensive training programmes, are crucial to mitigating these challenges. By addressing these issues, entrepreneurs in Lafia metropolis can better utilise social media to enhance their business activities and contribute to the region's economic growth.